Leaving care : throughcare and aftercare in Scotland - Dixon, Jo, 1967- (Jessica Kingsley Publishers, 2005)
How can social workers and agencies best support young people as they make the transition from care to independent living? This authoritative study explores the successes and failures of care services for young people, identifying factors that hinder effective transition from care and the types of support that help to promote positive life choices. Analysing current policy and drawing on the findings of past research, the authors explore the experiences of young people leaving the care of three very different Scottish local authorities to demonstrate how support works in practice. They address.